THE AGILITY AND COMPASSIONATE LEADERSHIP OF THE NEXT NORMAL (Malaysian Management Journal, 2023)
This research investigates insight into how leaders could lead the rising waters of the Covid-19 pandemic with agility and compassion.Based on pertinent literature, leaders must redefine their leadership mindset to harness team behavioural change toward team dynamics in organizational resilience. Through phenomenological research of eight companies’ leaders, a proposed model was presented to define the behavioural shift that facilitates leaders in orientating team mindset while embracing compassion. The next normal needs of the organization on the change of leaders’ behaviour, implying that building unique and pleasing agile and compassionate practices would lead to an improved organizational team workplace. This focuses on leaders’ efforts to empower teams through a cohesive concept to enable long-term team success. The research contributes to the body of knowledge through its constructivist approach and identification of underlying team dynamics pivotal for organizational resilience.